Assessing public awareness of myopia after the COVID-19 pandemic: an infodemiology study - Yan Zhang; Kazuo Tsubota; Kazuno Negishi; Toshihide Kurihara; Junhan Chen; Deokho Lee; Shin-ichi Ikeda (BMJ Health & Care Informatics)
Objectives Since the COVID-19 pandemic started, an increasing number of individuals use online resources to obtain health-related information, including myopia management. We aimed to obtain the search interest of global public health on myopia and prevention/treatment methods before and after the outbreak of COVID-19.Methods Google Trends was used to assess the global search interest in myopia and related terms. Data spanning from 2019 to 2023 were collected and segmented into three periods: prepandemic (2019), pandemic year (2020) and postpandemic (2021–2023). Each average search volume index was used to examine public awareness with the Kruskal-Wallis test.Results Among commonly used search keywords, Myopia is preferred over more colloquial terms (Nearsighted and Shortsighted). During the pandemic, searches for Myopia remained stable, while postpandemic, interest in Myopia surged (31.54%, p<0.0001). Myopia prevention/treatment awareness from 2019 to 2023 indicated notable shifts. In 2020, searches for Contact lenses and Spectacles decreased (−14.09% and −21.97%, respectively, both p<0.0001). These trends persisted postpandemic, with declining searches for Orthokeratology (−41.38%, p<0.01). Public interest for Light therapy (43.00%, p<0.0001) and Atropine (27.42%, p<0.0001) increased.Discussion The research highlights significant increases in global online awareness of myopia during the COVID-19 pandemic. The extended period of remote work during the pandemic may alter lifestyle habits and affect public perception of treatment options. Those findings could offer valuable perspectives on global interest patterns related to myopia, which supports subsequent myopia studies and is further useful to develop relevant public health policies.